Implementation evaluation of the family hope program in support of basic education - Idelia Marzuki, Apri Wahyudi, Zulela, Arita Marini,; Mahmudi, Silfiana Nur Barokah, (Opción, 2019)
This study aims to evaluate the implementation of the Family Hope Program (PKH) in improving the quality of education in Indonesia by use of an evaluation model context, input, process, product (CIPP) as a method. CIPP survey sent to students and parents, teachers, principals, Department of Education and Social Service who has a response rate context for 95%, Input for 95%, Process for 97.5% and Product of 92.5%. In conclusion, the implementation of the CCT fully meets the needs of students in support of Basic Education of Metro City.